2019
DOI: 10.1021/acs.jced.8b00891
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibrium for Ternary Systems of Polyoxymethylene Dimethyl Ethers + o-Xylene + Water at 293.15 K

Abstract: Polyoxymethylene dimethyl ethers (PODE n ) are excellent diesel blending components which can eliminate exhaust gas emissions compared to conventional diesel. During the production process of PODE n from methanol and formaldehyde solution, the most important key is to find an appropriate phenomenon for the separation of water and formaldehyde from PODE3–6 in advance. In this work, ternary liquid–liquid equilibrium (LLE) data were determined at T = 293.15 K under atmospheric pressure for the following systems:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Compared with the regression results of the UNIQUAC model, the deviation of the NRTL model is relatively small, indicating that the NRTL model has better consistency for the ternary system. At the same time, it can be seen that in Figures –, there is good agreement between the calculated data and the experimental data. , …”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Compared with the regression results of the UNIQUAC model, the deviation of the NRTL model is relatively small, indicating that the NRTL model has better consistency for the ternary system. At the same time, it can be seen that in Figures –, there is good agreement between the calculated data and the experimental data. , …”
Section: Resultssupporting
confidence: 65%
“…37,38 4. CONCLUSIONS LLE values regarding n-heptane + phenols + furfural systems were investigated at 101.3 kPa at 303.2, 323.2, and 343.2 K. The results indicated that furfural showed extraction capacity for phenol extraction from n-heptane solution.…”
mentioning
confidence: 99%
“… a Standard uncertainties u are u ( T ) = 0.1 K, u ( p ) = 2.3 kPa, u ( w ) = 0.0003. b The binary data were taken from the interpolated data in the literature c The binary data was taken at 303.2 K of the data from the literature d Relative deviation: δ = 100 × ( w exp – w lit )/ w exp . …”
Section: Resultsmentioning
confidence: 99%